2017
DOI: 10.1177/1056789517735679
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental and numerical analysis on the seismic behavior of short reinforced concrete columns with different structural sizes and axial compression ratios

Abstract: The results of an experimental program on eight short reinforced concrete columns having different structural sizes and axial compression ratios subjected to monotonic/cyclic lateral loading were reported. A 3D mesoscopic simulation method for the analysis of mechanical properties of reinforced concrete members was established, and then it was utilized as an important supplement and extension of the traditional experimental method. Lots of numerical trials, based on the restricted experimental results and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 63 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…On the one hand, in engineering projects, the side lengths of square columns are usually no less than 400 mm. On the other hand, Liu studied the size effect of seismic performance of RC columns and found that the deformability of RC columns decreased with the increase in size of RC columns [20]. Thus, studies about the seismic behaivour of confined concrete with side length no less than 400 mm are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, in engineering projects, the side lengths of square columns are usually no less than 400 mm. On the other hand, Liu studied the size effect of seismic performance of RC columns and found that the deformability of RC columns decreased with the increase in size of RC columns [20]. Thus, studies about the seismic behaivour of confined concrete with side length no less than 400 mm are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, various kinds of two-scale modeling methods have been successfully applied in the damage and failure analysis of civil structures under earthquakes [16][17][18][19][20]. Moreover, the mesoscale modeling approach has been successfully applied in the numerical simulation of concrete structures subjected to various loading cases [21][22][23]. The feasibility of XFEM-based multiscale models composed of two-scale and mesoscale models needs to be further investigated to provide an efficient way to analyze the structural behavior of RC structures.…”
Section: Introductionmentioning
confidence: 99%
“…Similar work includes Feng et al (2018) and Palermo and Trombetti (2016). Note that damage mechanics have also been widely applied to the modeling of concrete materials under static (Chen et al, 2018;Jin et al, 2018a;Li and Wu, 2018;Suchorzewski et al, 2018;Vorobiev et al, 2018), fatigue (Ding and Li, 2018), and dynamic (Hu et al, 2018;Jin et al, 2018bJin et al, , 2018cYang et al, 2019) loadings as well as harsh environments (Dong et al, 2018;Luo et al, 2018). The remainder of the paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%